Myeloid-derived suppressor cells and tumor escape from immune surveillance - Umansky, Viktor; Blattner, Carolin; Fleming, Viktor; Gebhardt, Christoffer; Altevogt, Peter; Utikal, Jochen (Seminars in immunopathology, 2017)
Tumor progression is known to be supported by chronic inflammatory conditions developed in the tumor microenvironment. It is characterized by the long-term secretion of various inflammatory soluble factors (including cytokines, chemokines, growth factors, reactive oxygen and nitrogen species, prostaglandins, etc.) and strong leukocyte infiltration. Among leukocytes infiltrating tumors, myeloid-derived suppressor cells (MDSCs) represent one of the most important players mediating immunosuppression and supporting tumor escape. These cells can strongly inhibit antitumor immune reactions mediated by T cells and NK cells. Moreover, MDSCs are generated, recruited to the tumor site, and activated not only under the influence of soluble inflammatory mediators but also due to extracellular vesicles (EVs) secreted by tumor cells. EVs play a key role in the formation of MDSCs via the conversion of normal myeloid cells and altering the normal myelopoiesis. In addition, EVs help create a suitable microenvironment for the metastatic process.
Gesehen am 04.10.2018
Article was published online on 27 October 2016